Evaluación del proceso de obtención de una biopelícula a partir de pectina extraída de la pulpa de café arábica (2021)
When processing coffee, by-products are produced that generate environmental problems, one of them is the pulp, which contains a high content of pectin, a polysaccharide that can be used in the production of biofilms in order to replace highly polluting synthetic polymers, conferring properties biodegradable to the material. In the present work, the extraction process of pectin from Arabica coffee pulp was studied, for its subsequent application in obtaining a biofilm. To establish the optimal conditions of the extraction process, a 23 factorial design of experiments was carried out where the factors were: pH, temperature and extraction time. The process for obtaining Arabica coffee pectin was carried out by means of an acid hydrolysis developed at a pH of 1, a temperature of 90 ° C and a time of 40 minutes; a yield of 5.39% was recorded on a dry basis.